Optimizing dental implant design: Structure, strength, and bone ingrowth - Jenny Zwei-Chieng Chang; Jui-Ting Hsu; Ming-Jun Li; Hung-Ying Lin; Jason Sun; Nien-Ti Tsou; Jui-Sheng Sun (Journal of Dental Sciences)
Background/purpose: Replacing missing teeth with implant-supported prostheses is a common practice; however, function-induced early bone loss may exacerbate peri-implantitis. Identifying factors that influence marginal bone loss is crucial. This study used finite element (FE) simulation and in-vitro analysis to evaluate design concepts and their effects on stresses and strains in dental implants and surrounding bone. Materials and methods: Five implant designs were analyzed: (1) full solid, (2) upper porous, (3) lower porous, (4) lower porous: upper half, and (5) lower porous: lower half. The study included stability measurements, three-dimensional FE modeling, in-vitro mechanical testing, and simulations of long-term bone remodeling. Results: The full-solid design showed the highest stress tolerance, followed by the lower porous and upper porous designs. Stress concentration was higher with oblique forces. The upper porous design favored bone strain distribution but exhibited permanent deformation beyond 350 N. Lower porous implants demonstrated similar strength to the full solid but superior marginal bone growth. Conclusion: Within the scope of this study, the following conclusions were drawn: (1) A well-designed porous structure enhances post-implantation bone growth; (2) An upper porous design facilitates bone ingrowth but exhibits reduced strength under stress; (3) Lowering porosity adversely affects bone regeneration.